L’égalité devant les charges publiques jako podstawa odpowiedzialności państwa na zasadzie słuszności w prawie francuskim - Jaworski, Bartłomiej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
State liability on equity is a legal institution, guaranteeing citizens a possibility of acquiring compensations for damages resulting from legitimate actions of the public authority. In the Polish legal system it is regulated by art. 4172 of the Act – Civil Code and is an element of a panel of regulations art. 417–420 of the Civil Code, standardising the issues of liability of the public authority. Article 4172 has a special and auxiliary character, considering the liability for a damage caused by the public authority as a result of its legal actions as a revision of liability on general terms. In the French law the counterpart of the Polish principle of equity is the principle of equity before public burdens (l’égalité devant les charges publiques), which is the basis for the authority’s liability for legal actions. This non-code construction, being a domain of the administration law, was shaped in France especially by the case law of the Council of State and the Court of Competence and today is used to settle damages caused during hospital treatment, based on equity to the public hospital. This institution is similar to the Polish one but the commonness of its usage in France, as well as its non-code character, are sufficient reasons to conduct an in-depth research in that regard.
Keywords: the principle of equity under French law; state liability on equity; principle l’égalité devant les charges publiques